2019
DOI: 10.20525/ijrbs.v8i4.277
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Work Culture, Suitability of Tasks, Leadership Style That has an Impact on Performance

Abstract: This study is designed to analyze the perceptions and executions of work culture, the suitability of tasks, andleadership style that would have an impact on performance by using job satisfaction as mediating these conditions. This research was conducted at the Regional Office of the Directorate General of State Wealth (DJKN) in the Aceh Province. Primary data is obtained by circulating questionnaires to 121 workers on the institutions mentioned above using the census method. The primary data from the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Motivational work behavior plays a mediating role between them and is completely intermediary; the psychological capital of university teachers cannot directly affect job thriving of university teachers. According to the previous research (Anastasia & Pawan, 2010) and the combination of related theories (Muhammad et al, 2019), psychological capital should have an influence on job thriving through motivational work behaviors, and the theoretical model has also been confirmed. This conclusion is unique in that it mainly uses empirical methods to prove that psychological capital affects the job thriving of university teachers and reveals that the psychological capital has a positive effect on job thriving, which is useful for the future development and cultivation of teachers' psychological capital in China.…”
Section: Discussionmentioning
confidence: 75%
“…Motivational work behavior plays a mediating role between them and is completely intermediary; the psychological capital of university teachers cannot directly affect job thriving of university teachers. According to the previous research (Anastasia & Pawan, 2010) and the combination of related theories (Muhammad et al, 2019), psychological capital should have an influence on job thriving through motivational work behaviors, and the theoretical model has also been confirmed. This conclusion is unique in that it mainly uses empirical methods to prove that psychological capital affects the job thriving of university teachers and reveals that the psychological capital has a positive effect on job thriving, which is useful for the future development and cultivation of teachers' psychological capital in China.…”
Section: Discussionmentioning
confidence: 75%
“…Research by Platis et al (2015) found that there is a strong and positive correlation between job satisfaction and performance in health services. Furthermore, the analysis results of research by Ritonga et al, (2019) showed that there was an effect of job satisfaction on employee performance, indicated by the estimated standard value above 0.50, namely 0.589. The results of this study are in accordance with previous research conducted by Parwanto and Wahyudi (cited in Devi, 2018) which found that job satisfaction factors consisting of salary, leadership, co-workers' attitudes showed a significant effect on employee performance.…”
Section: A the Effect Of Job Satisfaction On The Performance Of Uinsi...mentioning
confidence: 98%
“…Work culture, job fit, and leadership style all influence performance favorably according to Ritonga et al (2019) and Azanza et al (2013) argues, the first dimension of organizational culture focuses on the organization from the perspective of its people and their relationships with one another, while the second focuses on flexibility, decentralization, and control while maintaining stability.…”
Section: Literature Reviewmentioning
confidence: 99%